A model for germanium-silicon equilibrium fractionation in kaolinite. (1st November 2020) - Perez-Fodich, Alida; Derry, Louis A.
Abstract: Germanium is a useful tracer of silicate weathering and secondary mineral formation in the Critical Zone because Ge/Si ratios are fractionated during incongruent weathering of silicates. We develop an estimate of the equilibrium fractionation coefficient between germanium and silicon for the precipitation of kaolinite using a solid-solution model. Thermodynamic properties and distribution coefficient were estimated using observations from natural systems, experimental data from analog phyllo-germanate minerals (Shtenberg et al., 2017) and a parametric method based on a sum of oxides approach with site-specific interaction parameters (Blanc et al., 2015). The estimated log D G e - S i ' for the incorporation of Ge into kaolinite at 25 °C and 0.1 MPa is equal to −3.4 ± 1.5. The estimated Δ G f ° for a fully Ge substituted kaolinite ( Ge 2 Al 2 O 5 ( OH ) 4 ) equals −3130 ± 15 (kJ/mol) and the estimated log K s p for Ge-kaolinite = 3.1 ± 1.5. We further develop a series of batch reaction models using a geochemical reactive transport code to test the estimated range of the Ge-Si equilibrium fractionation coefficient. In these series of models, we also investigate how precipitation dynamics can impact the Ge/Si ratios observed both in streams and soils. These models show that both precipitation kinetics and re-equilibration of the precipitated solid control the behavior of Ge/Si ratios at far-from-equilibrium timescales. While the actual length of these timescales remains to be determined by better constraints on kaolinite precipitation rates at environmental conditions; our models suggest that the lowest groundwater measured Ge/Si ratios should represent this equilibrium timescale.